2016
DOI: 10.1371/journal.pone.0163598
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar tDCS Does Not Improve Learning in a Complex Whole Body Dynamic Balance Task in Young Healthy Subjects

Abstract: Transcranial direct current stimulation (tDCS) of the cerebellum is of increasing interest as a non-invasive technique to modulate motor performance and learning in health and disease. Previous studies have shown that cerebellar tDCS facilitates reach adaptation and associative motor learning in healthy subjects. In the present study it was tested whether cerebellar tDCS improves learning of a complex whole body motor skill. Because this task involves learning of posture and balance likely including learning o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 27 publications
4
61
3
2
Order By: Relevance
“…2020; 22(3):e96259. a-tDCS of the cerebellum had no significant effects on balance (25)(26)(27). These controversial findings show that age is a factor, which may affect the outcomes of brain stimulation techniques (7,28,29).…”
Section: Effect Of Cerebellar Tdcs On Balancementioning
confidence: 95%
“…2020; 22(3):e96259. a-tDCS of the cerebellum had no significant effects on balance (25)(26)(27). These controversial findings show that age is a factor, which may affect the outcomes of brain stimulation techniques (7,28,29).…”
Section: Effect Of Cerebellar Tdcs On Balancementioning
confidence: 95%
“…The faster and more efficient postural adaptation induced by active stimulation, warrants exploration of this type of intervention in combination with behavioral training in elderly individuals or patient populations with impaired postural balance (e.g., Parkinson's disease or stroke). It needs to be noted that several recent studies failed to find positive effects of ctDCS on postural control (e.g., Steiner et al 2016) or reported positive effects of inhibitory cathodal ctDCS (e.g., Inukai et al 2016). However, the protocol used in the latter study substantially deviated from our study (e.g., regarding stimulation parameters, outcome measures, visual cues) and only assessed ctDCS effects on quiet standing performance (i.e., no disturbance requiring adaptive postural control was investigated).…”
Section: Current Modelingmentioning
confidence: 99%
“…However, the protocol used in the latter study substantially deviated from our study (e.g., regarding stimulation parameters, outcome measures, visual cues) and only assessed ctDCS effects on quiet standing performance (i.e., no disturbance requiring adaptive postural control was investigated). Likewise, while the study by Steiner et al (2016) involved learning of a complex motor skill, the authors speculated that their healthy young subjects may have performed at "maximum possible learning level", which may have prevented further improvement by ctDCS. Nonetheless, these studies highlight that multiple factors that are currently not well understood mediate ctDCS response (van Dun et al, 2016).…”
Section: Current Modelingmentioning
confidence: 99%
“…Additionally, it was demonstrated that CB-tDCS elicits improvements in postural control, both in healthy participants [31] as well as chronic stroke patients [32]. Nevertheless, some studies show no effects of CB-tDCS on balance control in healthy participants [32,33]. To date, no study has tested the effects of CB-tDCS on core features of muscle strength, such as MIVC.…”
Section: Introductionmentioning
confidence: 99%